ANALISA KEEFEKTIFAN DESIGN SIGN SYSTEM PADA KAWASAN WISATA GOA PUTRI BATURAJA - Marandika, Aldo Handani; Hukubun, Lejar Daniartana; Doni Fitri, Nofria; Syamsi, Mohammad Danang; Kusumohendrarto, Raden Hadapiningrani (AKSA: Jurnal Desain Komunikasi Visual, 2025)
Sign systems play a role in supporting the convenience, comfort, and experience of visitors in an area, including tourist attractions. Goa Putri Baturaja is a tourist destination in South Sumatra and already has a sign system. This study aims to analyze the effectiveness of the sign system in the Goa Putri tourist attraction on the convenience and suitability with the installation environment in the area. The approach in this study is the observation and qualitative descriptive method, supported by the analysis of the sign system design. The results of this study indicate that the sign system in Goa Putri Baturaja is still less effective, especially as a direction indicator, and less in accordance with the characteristics of the surrounding environment. Several factors that influence this effectiveness include readability, material selection, placement, and suitability of the design to the surrounding natural context. The findings of this study indicate that it is necessary to improve the design of the sign system that takes into account visual aspects, installation location, materials, and visitor needs to improve overall comfort and tourist experience.